Combination of CDF and D0 measurements of the W boson helicity in top quark decays - Cdf, T; Collaborations, D; Aaltonen, T; Abazov, V; Abbott, B; Acharya, B; Adams, M; Adams, T; Alexeev, G; Alkhazov, G; Alton, A; González, B; et al. (2012)
We report the combination of recent measurements of the helicity of the W boson from top quark decay by the CDF and D0 collaborations, based on data samples corresponding to integrated luminosities of 2.7 - 5.4 fb^-1 of ppbar collisions collected during Run II of the Fermilab Tevatron Collider. Combining measurements that simultaneously determine the fractions of W bosons with longitudinal (f0) and right-handed (f+) helicities, we find f0 = 0.722 \pm 0.081 [\pm 0.062 (stat.) \pm 0.052 (syst.)] and f+ = -0.033 \pm 0.046 [\pm 0.034 (stat.) \pm 0.031 (syst.)]. Combining measurements where one of the helicity fractions is fixed to the value expected in the standard model, we find f0 = 0.682 \pm 0.057 [\pm 0.035 (stat.) \pm 0.046 (syst.)] and f+ = -0.015\pm0.035 [\pm 0.018 (stat.) \pm 0.030 (syst.)]. The results are consistent with standard model expectations.